Large-scale synthesis of colloidal bowl-shaped particles. Issue 25 (7th June 2021) - Edmond, Kazem V.; Jacobson, Tess W. P.; Oh, Joon Suk; Yi, Gi-Ra; Hollingsworth, Andrew D.; Sacanna, Stefano; Pine, David J.
Abstract : We describe a general procedure for the large-scale fabrication of bowl-shaped colloidal particles using an emulsion templating technique. Abstract : We describe a general procedure for the large-scale fabrication of bowl-shaped colloidal particles using an emulsion templating technique. Following this method, single polymeric seed particles become located on individual oil droplet surfaces. The polymer phase is subsequently plasticized using an appropriate solvent. In this critical step, the compliant seed is deformed by surface tension, with the droplet serving as a templating surface. Solvent evaporation freezes the desired particle shape and the oil is subsequently removed by alcohol dissolution. The resulting uniformly-shaped colloidal particles were studied using scanning electron and optical microscopy. By adjusting the droplet size and the seed particle diameter, we demonstrate that the final particle shape can be controlled precisely, from shallow lenses to deep bowls. We also show that the colloid's uniformity and abundant quantity allowed the depletion-mediated assembly of flexible colloidal chains and clusters.